2006
DOI: 10.1086/506363
|View full text |Cite
|
Sign up to set email alerts
|

Measles‐Virus–Neutralizing Antibodies in Intravenous Immunoglobulins

Abstract: Measles infection induces lifelong immunity; however, wild-type infection stimulates higher levels of measles-virus-neutralizing antibodies (mnAbs) than does vaccination. Because the proportion of the donor population with vaccine-induced measles immunity is increasing, this study was conducted to determine whether this shift in demographic characteristics affects mnAb levels in contemporary lots of Immune Globulin Intravenous (Human) (IGIV). When 166 lots of 7 IGIV products manufactured between 1998 and 2003 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
0
3

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 21 publications
4
38
0
3
Order By: Relevance
“…Kiovig, GGЈLQD contain even higher (Pϭ0.0286) neutralizing CMV antibody titers than GGЈSD, quite possibly reflecting the more modern manufacturing process used for the production of these products compared with GGЈSD (15). Among other factors, the virus neutralization capacity of a final IgG product possibly depend on the specific manufacturing processes, for example, protease treatments and other downstream procedures, which may differentially affect the preservation of specific IgG subclasses and consequently antibody titers (16). Therefore, the higher CMV neutralization capacity as determined for IVIG preparations developed more recently may result from improved manufacturing processes that better preserve the physiological IgG subclass distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Kiovig, GGЈLQD contain even higher (Pϭ0.0286) neutralizing CMV antibody titers than GGЈSD, quite possibly reflecting the more modern manufacturing process used for the production of these products compared with GGЈSD (15). Among other factors, the virus neutralization capacity of a final IgG product possibly depend on the specific manufacturing processes, for example, protease treatments and other downstream procedures, which may differentially affect the preservation of specific IgG subclasses and consequently antibody titers (16). Therefore, the higher CMV neutralization capacity as determined for IVIG preparations developed more recently may result from improved manufacturing processes that better preserve the physiological IgG subclass distribution.…”
Section: Discussionmentioning
confidence: 99%
“…A similar association of vaccine-induced immunity and concomitant decrease in specific antibody titers has already been associated with measles vaccination and the decrease of measles antibodies in US IVIG. 29 Because the IVIG preparations made of EU and US plasma are both manufactured using the same process, 17 it was not surprising that the difference in HAV antibody content in EU-versus USsourced human plasma was reflected in the IVIG preparations made thereof (Fig 2, B). A similar difference in HAVantibody content has previously been noted during an evaluation of antibody quantities in United Kingdom-and US-sourced immune globulins.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of lower levels of neutralizing TBEV Abs in Russian-IVIG cannot be due to the difference in circulating TBEV subtypes between Europe and Russia (35) or the use of a European subtype TBEV strain for the neutralization experiments reported here, as it has been shown that vaccination with any of the three TBEV subtypes raises Abs that are also cross-neutralizing against the other subtypes (15, 23, 39). As IgG3 has the highest neutralization effect for, e.g., dengue virus (32), cytomegalovirus (11), and rubella and polioviruses (3) and IgG3 degradation during manufacture has been a problem in narrow-spectrum IVIG products (1,27,37), the IgG3 content was determined for the three Russian-IVIG lots by enzyme-linked immunosorbent assay (ELISA), as previously described (14). The results (data not shown) showed IgG3 content that was within the physiological range, and IgG3 degradation could therefore be excluded as a contributing factor for the reduced TBEV neutralization capacity of the Russian-IVIG.…”
mentioning
confidence: 99%